Perbandingan Akad Bagi Hasil Pada Akad Pembiayaan Musyarakah di Bank Syariah dan Fintech Syariah - Mulyana, Iwan (Banking & Management Review, 2020)
The implementation of musharaka Financing in sharia fintech is more complex compared to musharaka Financing in sharia banks. This study aims to determine the comparison of the contract and the consequences of the method of calculating the profit sharing ratio that is applied to the musharaka Financing in fintech syariah compared to musharaka Financing in islamic banks. The research method used is comparative descriptive qualitative research. Data collection techniques are in the form of documentation studies, analysis of data from fintech mobile applications, and interviews. The data used are the regulations and customer data at the BJB Syariah Bank and at PT Ammana Fintech Syariah. The results of this study are that in Financing in Islamic banks, there is only a musharaka Financing contract with the consequence that the calculation of profit sharing ratio is not so complicated. On the other hand, in the musharaka Financing in Sharia fintech there is another contract so that the musharaka contract becomes complete. This is due to the fact that there are at least 4 parties in Sharia fintech Financing, namely: fund managers, agents, funders and the fintech company itself with the consequence there are other calculations outside the profit sharing ratio. The conclusion of this study is that the calculation of profit sharing ratio in fintech is not much different from the calculation of ratio in islamic banks. What makes the difference is only the addition of the contract in order to strengthen the musharaka contract. Keywords: Musharaka, Islamic Fintech, Islamic Financing.